Breeding of Lipoxygenase-1-less Malting Barley Variety CDC PolarStar and Effect of Lipoxygenase-1-less Trait on Beer Quality at Pilot and Commercial Scale Brewing - Hoki, Takehiro; Saito, Watanu; Hirota, Naohiko; Shirai, Masanori; Takoi, Kiyoshi; Yoshida, Shinichiro; Shimase, Masayuki; Saito, Tetsuya; Takaoka, Tomokazu; Kihara, Makoto; Yamada, Shinji (BrewingScience, 2013)
CDC PolarStar was successfully developed as the first lipoxygenase-1-less (LOX-less) malting barley variety in North America by successive backcross and molecular marker assisted selection (MMAS). The yield potential, the agronomic performance and the general malting quality of CDC PolarStar were equivalent to those of the recurrent parent CDC Kendall which was one of well evaluated and accepted two-rowed malting barley varieties in North America. These are very important findings to demonstrate that the LOX-less trait could be used for barley breeding to improve beer quality without affecting such characteristics. To evaluate effects of LOX-less trait on beer quality, several brewing trials were conducted at the pilot and the commercial scale facilities. The wort and beer analyses indicated that the LOX-less trait did not have much effect on the characteristics which are expected not to be affected by absence of LOX-1 activity. In contrast, the beers made of CDC PolarStar malt showed reduced levels of beer deteriorating substances, such as trans-2-nonenal (T2N) and trihydroxyoctadecenoic acid (THOD) compared to the beers made of the control malt. The sensory evaluations by well-trained panelists showed the significant superiority of CDC PolarStar beers in terms of staleness in most trials and the positive effect of LOX-less trait was more apparent in low malt beer conditions. These results indicate that LOX-less barley variety CDC PolarStar can improve flavor stability without affecting any other beer characteristics.